Biochemical Characterization of Rare and Threatened Local Populations of Peas (Pisum sativum L.) Cultivated in the Arid Region of Southern Tunisia. Issue 12 (8th November 2022) - Mohamed, Amina; Tlahig, Samir; Moussa, Jamila Yehmed; Yahia, Leila Ben; Bouhamda, Talel; Loumerem, Mohamed
Abstract: Pea ( Pisum sativum L.) is an important legume for human and animal consumption, cultivated in many temperate regions of the world. In the present investigation, the seeds of twelve pea accessions collected from the arid regions of southern Tunisia, characterized by different colors of flowers and seed coats, were evaluated for their proteins, phenolic compounds and antioxidant activities. The protein content determined by the Bradford method ranged from 46.91 to 151.08 mg/g DW. The content of total phenol, total flavonoid and condensed tannin, ranging from 36.85 to 102.52 mg GAE/100 g DW, 6.95 to 48.11 mg QE/100 g DW, and 12.37 to 70.43 mg CE/100 g DW, respectively. These parameters were characterized respectively by the following three methods, the Folin‐Ciocalteu reagent, the aluminum chloride and the vanillin assay. The LC‐ESI/MS analysis identified the presence of 8 phenolic acids and 9 flavonoids which quinic acid, protocatechuic acid, hyperoside, and quercetin‐3‐O‐rhamnosidewere detected as the most abundant compounds. Moreover, the antioxidant activity of pea seeds was evaluated by the ABTS+and DPPH tests. Indeed, DPPH and ABTS anti‐free radical activity values ranged from 1.92 to 14.11 μmoL TEAC/g DW and 2.3 to 14.95 μmoL TEAC/g DW, respectively. The variability across the assessed traits revealed significant differences as computed by ANOVA tests. Else, the results showed significant correlations between seed coat color, seed shape, flower color and phenolic compounds. Therefore, genotypes characterized by a purple flower, brown seed coat, and wrinkled form had the highest levels of phenolic compounds and antioxidant activity. Correlation analysis revealed that phenolic compounds presented a strong positive correlation with antioxidant activities, while being negatively correlated with protein content. UPGMA cluster and Principal component analysis (PCA) revealed two main groups. This work highlights the nutritional value of P. sativum seeds as a good source of natural antioxidant compounds that may be useful in the food and pharmaceutical industries. Abstract :